PENGARUH KEGIATAN WISATA TERHADAP KUALITAS AIR SUNGAI SIBIRU BIRU KECAMATAN BIRU-BIRU KABUPATEN DELI SERDANG Effect of Tourist Activities on Water Quality In Sibiru Biru River District of Biru-Biru Regency of Deli Serdang. - Rawiyatul Hikmah; Ternala Alexander Barus; Rusdi Leidonald (AQUACOASTMARINE, 2015)
The biggest benefit river is for agricultural irrigation, drinking water, rain drains and atourist attraction. This research has been carried out on the Sibiru Biru River district of Biru-Biru regency of Deli Serdang in April-May 2015 by analyzing the influen of taurism travelactivity on water quality Sibiru Biru River and to know the perception of visitors and touristmanage of Sibiru Biru River. The parameters observed were current speed, watertemperature, TSS, DO, pH, BOD5, N, P and Total Coliform. The results are showed allparameters meet the water quality standards on PP No. 82 Tahun 2001 and the STORETscoring system. Sibiru Biru River based on STORET method for water quality standart classII with criteria very good/A (Score 0). Perceptions of visitors meet to the beaut of Sibiru BiruRiver amounting 57,5% or in categor of very beautiful of and the comfort level of 62.5% orin categor very confor. There are 100% or as much as 4 managers to provide cottage morethan 10 and there are 100% managers to handle waste from tourist activity by collecting andburned. There is no notice board which aims to urge tourists to maintain the cleanliness andstill insufficient number of garbage in Sibiru Biru River.Key word : Sibiru Biru River, water quality, perceptions of visitors, perceptions managers.